Analisis Pengaruh Pengetahuan dan Promosi terhadap Minat Menabung Masyarakat Muaro Sebo Ilir di Bank Syariah Indonesia Cabang Muaro Bulian - Dini Haryati (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study aims to analyze the influence of knowledge and promotion on interest in saving at Bank Syariah Indonesia (BSI) Muara Bulian Branch in the Maro Sebo Ilir community. Interest in saving at Islamic banks is influenced by various factors, including the level of public understanding of the Islamic banking system and the effectiveness of promotional strategies carried out by banks. This study uses a quantitative approach with a survey method, where data is collected through a questionnaire distributed to the people of Maro Sebo Ilir. The data analysis technique used is multiple regression analysis to determine the relationship and influence between independent variables, namely knowledge and promotion, on dependent variables, namely saving interest. The results of the study show that both knowledge and promotion have a positive and significant effect on the interest in saving at BSI Muara Bulian Branch. The higher the level of public knowledge about Islamic banking, the greater their interest in saving. Similarly, an effective promotional strategy can increase public awareness and interest in sharia savings products. Thus, BSI needs to increase education about Islamic banking and optimize promotional strategies to attract more customers. This research is expected to be a reference for Islamic banks in designing more appropriate policies to increase the number of customers.